PALEONTOLOGIA DE LOS SEDIMENTOS MARINOS HOLOCENOS DE LOS ALREDEDORES DE BAHIA BLANCA, PROVINCIA DE BUENOS AIRES (Ameghiniana, 2014)
In this work a systematical study of the faunal association found in the holocene marine sediments at Bahia Blanca area is given. About one hundred species of molluscs were determined, as well as foraminifera, corals, worms, ostracoda, cirripedia, decapoda, ophiuroidea and skeletal parts of chondrichthyes, osteichthyes and cetaceans. .Three new species of molluscs are described and figured: Cochliolepis surensis, Teinostoma maldonadensis y Gouldia camachoi; Puncturella conica (d'Orbigny) proved to have wider distribution. Also, three species of molluscs are mentioned for the first time for the Argentinean Quaternary: Turbonilla smithi Pfeffer, Turbonilla madrynensis Lamy and Periploma ovatum d'Orbigny.